Analisis Yuridis Arbitrase Perihal Tidak Dapat Ditanda Tanganinya Perjanjian Tertulis Oleh Para Pihak Yang Bersengketa - Muhammad Rudiansyah (Scholar Center, 2020)
In the dispute resolution process through arbitration is a settlement process outside the general court (non-litigation), where the settlement is based on an agreement. The agreement in question is a written agreement made by the parties, before or afterthe disputes. Article 9 paragraph (1) and (2) of Law Number 30/1999 onArbitration and Alternative Dispute Resolution explains that if in dispute resolution through arbitration the arbitration agreement cannot be signed, it can be replaced with an authentic deed (notary deed). However, there is no explanation onthe specific reasons that allow the agreement to be replaced by a notary deed. The method used is this study is a normative research method The result of this research is that there is still legal obscurity in the provisions of Article 9 paragraph (1) and (2) which still does not include the reasons that the parties may not sign the agreement and be replaced with an authentic deed. It is necessary to emphasize the purpose of the provisions of Article 9 paragraphs 1 and 2.